Biologics in severe asthma: the role of real-world evidence from registries. (8th June 2022) - Paoletti, Giovanni; Pepys, Jack; Casini, Marta; Di Bona, Danilo; Heffler, Enrico; Goh, Celine Y.Y.; Price, David B.; Canonica, Giorgio Walter
Asthma is one of the most common noncommunicable diseases; in the majority of patients it is well controlled with inhaled bronchodilators and inhaled corticosteroids, but the management of severe asthma has been a significant challenge historically. The introduction of novel biologic drugs in the past few decades has revolutionised the field, presenting physicians with a variety of biologic drugs with different mechanisms for the treatment of severe asthma. It is of crucial importance to evaluate the effectiveness of these drugs by following their "real-life" effectiveness rather than relying solely on their efficacy, established in carefully designed clinical trials, which therefore do not necessarily match the profile of the real-life patient. Understanding the actual effectiveness of the specific drugs in real-life patients is a crucial part of tailoring the right drugs to the right patients. Registries serve as an important tool in obtaining real-life evidence, since they are in effect observational studies, following the entire patient population. Data on long-term efficacy and safety of biologics in severe asthma cannot be obtained by RCTs alone. Real-life studies should be a valuable source of this kind of information. https://bit.ly/3vM8AaD